Financial Inclusion and Economic Growth Nexus, Evidence from Nigeria - Obademi , Emmanuel Olalekan; Adeniran, Christiana (Unilag Journal of Humanities, 2019)
This study focuses on the impact of financial inclusion on economic growth in Nigeria. Primary data was gathered with the aid of questionnaires which consists of a sample size of 180. Two hundred and twenty (220) questionnaires were distributed among individuals, owners of small and medium scale enterprises within Nigeria, but one hundred and eighty were retrieved representing a response rate of 81.81%. Simple linear Regression analysis was used in testing the three hypotheses: local credit influence on economic growth, effect of financial inclusion on economic growth and the impact of commercial bank deposits on economic growth, our findings showed that there is significant relationship between local credit and economic growth in Nigeria, It was also found in this study that there is significant relationship between financial inclusion and economic growth and that there is significant relationship between commercial bank deposits and economic growth. Environmental factors have an impact on planning and forecasting in business management and there was a positive relationship between planning and forecasting. This was reviewed through the response obtained. I, therefore recommend that Central Bank of Nigeria should increase its vigor for pursuing financial inclusion as it not only helps with economic growth as espoused in literature, but also effectuates monetary policy in Nigeria.